Fine-Tuning of Mast Cell Activation by FcεRIβ Chain - Ra, Chisei (Frontiers Research Foundation, 2012)
Mast cells play a key role in allergic reaction and disorders through the high affinity receptor for IgE (Fc(ε)RI) which is primarily activated by IgE and antigen complex. In humans, mast cells express two types of Fc(ε)RI on the cell surface, tetrameric αβγ(2) and trimeric αγ(2), whereas in mice, the tetrameric αβγ(2) type is exclusively expressed. In human allergic inflammation lesions, mast cells increase in number and preferentially express the αβγ(2) type Fc(ε)RI. By contrast, in the lesion of non-allergic inflammation, mast cells mainly express the αγ(2)type. Since the β chain amplifies the expression and signaling of FcεRI, mast cell effector functions and allergic reaction in vivo are enhanced in the presence of the β chain. In contrast, a truncated β chain-isoform (βT) inhibits FcεRI surface expression. The human Fc(ε)RIβ gene contains seven exons and a repressor element located in the forth intron, through which Fc(ε)RIβ transcription is repressed in the presence of GM-CSF. Regarding the additional signal regulatory function of the β chain, the β chain ITAM has dual (positive and negative) functions in the regulation of the mast cell activation. Namely, the Fc(ε)RIβ chain ITAM enhances the mast cell activation signal triggered by a low-intensity (weak) stimulation whereas it suppresses the signal triggered by high-intensity (strong) stimulation. In an oxazolone-induced mouse CHS model, IgE-mediated mast cell activation is required and the β chain ITAM is crucially involved. Adenosine receptor, one of the GPCRs, triggers a synergistic degranulation response with FcεRI in mast cells, for which the β chain ITAM critically plays positive role, possibly reflecting the in vivo allergic response. These regulatory functions of the FcεRIβ ITAM finely tune FcεRI-induced mast cell activation depending on the stimulation strength, enabling the Fc(ε)RIβ chain to become a potential molecular target for the development of new strategies for therapeutic interventions for allergies.